What does restorative justice promise? - Hollósvölgyi, Máté (European journal of probation, 2025)
In Hungary, restorative justice involves a wide range of professionals: probation officers, police, lawyers, judges, prosecutors, social workers, and teachers—alongside potential offenders and their communities. This approach raises key questions: How can so many stakeholders work together across disciplines towards a common goal? How can conflict be used to strengthen community bonds? Can justice be achieved by addressing and repairing harm? These questions guide the exploration of restorative justice as a modern element in criminal justice. This paper examines Hungary’s mediation system within the Probation Service, focusing on how mediation functions and its role in justice. Since January 1, 2007, mediation has been available nationwide, adding new responsibilities to probation officers’ work. We review the tasks of these officers in mediation, assess their effectiveness, and analyze how mediation supports reintegration in the justice system, aiming to repair harm and foster accountability among offenders within their communities.